Formulation, Storage Possibilities, and Chemical Composition of Ready-to-Eat Honey-Tahena Paste - EL-SHAHALY, A. A.; MOHAMED, M. S.; EL-ZALAKI, ESTMAT M.; MOHASSEB, ZEINAB S. (The Libyan Journal of Agriculture, 2023)
The formulation of ready-to-eat spreadable paste of honey (62.5%) and sesame seed butter tahena (37.4%) along with artificial honey flavour (0.1%) and various additives is described. The system is a multiphase with a predomenant oil — dispersed in a continuous polar phase. Tween 80 and glycerol mono-slearate at 1% each gave the best stabilizing effect. Sorbitol (3%) decreases the desiccation of the paste, and lecithin (2%) improved its texture and spreadability. Changes occurred in moisture, free fatty acids, peroxide value, oil separation, and organoleptic properties of the paste, upon storage up to 100days at 25°Cand 6°C. Storage at 6°C wasrecommendedforstoringthealuminum tubes containing the paste (30 grams per each). Moisture, protein, fat, carbohydrates, ash, iron, phosphorus and calcium contents of the paste were 8.00, 11.76, 23.10, 55.00, 2.00,0.024,0.501, and 0.114% respectively. The essential amino acids were quantitavely estimated.